A last round of coffee? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The surviving remnants of the wild arabica coffee plants growing in the highland rainforests of Southwest Ethiopia are under serious threat